BALTIC-NORDIC COMPARATIVE STUDY ON MATHEMATICSTEACHERS’ BELIEFS: DESIGNING RESEARCH INSTRUMENT TO DESCRIBE THE BELIEFS AND PRACTICES OF MATHEMATICS TEACHERS - Lepik, Madis; Pipere, Anita (Acta Paedagogica Vilnensia, 2011)
The article describes some aspects of the cross-cultural NorBa project “Mathematics teachers’ educational beliefs”.1 The aims of the study, its theoretical background as well as the development of the questionnaire are discussed. Some preliminary results on Estonian and Latvian mathematics teachers’ beliefs and their comparison are presented. Knowledge of teachers’ beliefs may reveal the specificity of teaching approaches and thus contribute to teachers’ education or curricular reforms.
Keywords: teachers’ beliefs; comparative study; constructivist approach; non-constructivist approach